Capital Structure, Corporate Taxation and Firm Age*. (7th March 2013) - Pfaffermayr, Michael; Stöckl, Matthias; Winner, Hannes
Abstract: This paper analyses the relationship between corporate taxation, firm age and debt. We adapt a standard model of capital structure choice under corporate taxation, focusing on the financing and investment decisions typically faced by a firm. Our model suggests that the debt ratio is associated positively with the corporate tax rate and negatively with firm age. Further, we predict that the tax‐induced advantage of debt is more important for older firms than for younger ones. To test these hypotheses empirically, we use a cross‐section of around 405, 000 firms from 35 European countries and 127 NACE three‐digit industries. In line with previous research, we find that a firm's debt ratio increases with the corporate tax rate. Further, we observe that older firms exhibit smaller debt ratios than their younger counterparts. Finally, consistent with our theoretical model, we find a positive interaction between corporate taxation and firm age, indicating that the impact of corporate taxation on debt increases over a firm's lifetime.